Ministernotomy for aortic valve replacement: technique and outcomes of 35 operations - D. Beshley; V. Averchuk; I. Protsyk; S. Lishchenko; A. Sterniuk; A. Babych; V. Pavlov; D. Averchuk; A. Ratych; S. Vyszynska; O. Zadoretska; O. Kobzarenko; et al. (Ukrainian Journal of Cardiovascular Surgery, 2016)
Minimal-access aortic valve replacement (AVR) has emerged as an alternative to conventional AVR and is increasingly utilized worldwide. It is known from existing literature that a small incision is associated with less postoperative pain and better respiratory function.From January 15 to March 22 of 2016, thirty-five adult patients underwent isolated aortic valve replacement through a minimally invasive approach. The group included 19 males and 16 females, with mean age of 63±21 years. EF was below 35% in 12 patients; in the rest 23, no disturbances of myocardial contractility were observed.We used an upper inverted «T» or «J» hemisternotomy to the 4th intercostal space. Cardiopulmonary bypass was established by direct ascending aortic cannulation and direct right atrial cannulation through another port in subxiphoid area. Aortic cross-clamp was applied through the incision. Antegrade cardioplegia was delivered directly through coronary orifices after aortotomy. Different types of mechanical and biologic prosthesis were implanted. The technique of implantation was the same as for the conventional approach through full sternotomy.Partial translocation of prosthesis in the area of non-coronary sinus was used in 9 patients with narrow aortic ring.There were three postoperative deaths. Two patients died of renal and respiratory failure because of predisposing factors. One patient died of acute type B aortic dissection that occurred intraoperatively. Three patients underwent conversion to median sternotomy.Minimal access aortic valve replacement at the beginning of the learning curve is less comfortable for the surgeon. Several surgical tips for incision and cannulation technique allow increasing the operative field.